Crime and Punishment - Warsinski, Maria Fuglevaag (Norway, 1998)
Utilizing clandestine footage, the director takes an unflinching look at the final days of Srebrenica till the UN's final pullout. Powerful interviews detailing the disparate views of combatants on both sides are woven together with vivid descriptions of the impossible journeys faced by the few civilians who made it out alive.